The Effect Of Environmental Performance, Industry Type, And Company Size On Carbon Emission Disclosure - Ida Ayu Ary Mahadewi; Ni Made Adi Erawati; Gusti Ayu Nyoman Budiasih; I Putu Sudana (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
Carbon emission disclosure is an essential component of carbon accounting, which mandates that companies measure, acknowledge, document, present, and reveal their carbon emissions. This investigation seeks to assess how environmental performance, industry classification, and company size affect the disclosure of carbon emissions. The research was conducted on non-financial firms that were publicly listed on the Indonesia Stock Exchange from 2019 to 2021. A total of 186 observations were made over a span of three years, and they were chosen through purposive sampling. The analytical approach employed in this study was Multiple Linear Regression Analysis. The findings of the analysis reveal that environmental performance has an adverse effect on the disclosure of carbon emissions, the industry type does not have a significant impact on carbon emission disclosure, and company size plays a role in influencing the disclosure of carbon emissions.